Lives Amid Violence Transforming Development in the Wake of Conflict - Schomerus, Mareike (Bloomsbury Academic, 2023)
Violent conflict and its aftermath are pressing problems, particularly for international development initiatives. However, the results of development in conflict contexts have generally been disappointing and their preventative potential thus questionable. Available Open Access, Lives Amid Violence argues that this is because practitioners adhere to a mental model that emphasises linearity, certainty, and causality, assuming that violence is best addressed through work plans that deliver state-building, stabilisation and services. Based on ten years of multi-method research from, in, and on conflict-affected countries, this book challenges this approach. Drawing on a significant collaborative body of scholarship, this work puts forward original and generalizable conclusions about how lives amid violence persist, offering an invitation to abandon restricting mental models and to embrace creative ways of thinking and working. These include paying attention to the long-term effects of conflict on individual behaviour and decision-making, the social realities of economic life, the role service delivery plays in negotiations between citizens and states, and to creating meaningful relationships. Transformation also requires reflection and therefore the book concludes with constructive suggestions on how to practice these insights to better support those whose lives are shaped by violence. More details are available at www.transformingdevelopment.org The eBook editions of this book are available open access under a CC BY-NC-ND 3.0 licence on bloomsburycollections.com.